China's outward foreign direct investments and impact on the world economy - Yao, Shujie, (Nottingham China Policy Institute series., 2014)
"With its GDP rivalling that of the US, China is fast becoming the world's largest economy. China's foreign exchange reserves have increased rapidly alongside it's economic development, and it has become one of the largest recipients of foreign direct investment. This study makes useful contributions to existing literature on China's outward investment's by examining the causes and consequences of China's outward foreign direct investment (OFDI) explosion. It is the first of its kind to introduce a partial stock adjustment model to examine the dynamic adjustment of China's OFDI.The authors provide a comprehensive view of the development of China's OFDI by comparing the early period of 1991-2000 and the more recent period of 2003-2009. Through the use of case studies and modeling approaches the authors examine the effects of China's outward investment on individual companies or industrial sectors. They study the underlying motivations and locational determinants of China's OFDI, the impact on other source countries' OFDI in the host countries, and the dynamic adjustment of China's OFDI and its relationship with China's inward foreign direct investment (IFDI). The two case studies on Chinalco's investment in Rio Tinto and Geely's acquisition of Volvo reveal two important motivations of Chinese firms: resource-seeking and technological seeking. The modelling results show that China's outward investments have had significant displacement effect on OECD countries' investments. In contrast to many media commentaries, the authors suggest that such effects are not resources-oriented. Finally, the study examines the motivation behind China's outward investments, and suggests that China has implemented a national policy to promote overseas investment for two reasons: national security and national status as a business power.This study focuses on the development of China's OFDI and the examines the impact it has on the world economy. It will be an indispensable tool for sch